2012
DOI: 10.1007/s11655-011-0901-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Vaccinium uliginosum on rabbit retinal structure and light-induced function damage

Abstract: VU can relieve the injury to rabbit retinae exposed to normal day and night rhythm, alleviate the harm caused by light when used beforehand, and repair the light damage to the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Experimental studies in ophthalmology are often performed on the eyes of rabbits due to their similar size and the ease of making clinical observations without additional specialized equipment [ 63 , 64 ]. On the other hand, the rabbit retina has significant differences from the human retina (merangiotic type of the retina, absence of the macular area, and different distribution of photoreceptors of various types) [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in ophthalmology are often performed on the eyes of rabbits due to their similar size and the ease of making clinical observations without additional specialized equipment [ 63 , 64 ]. On the other hand, the rabbit retina has significant differences from the human retina (merangiotic type of the retina, absence of the macular area, and different distribution of photoreceptors of various types) [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that Vaccinium uliginosum extract prevented the blue light-induced human retinal pigment epithelial cell death by inhibiting photo-oxidation of N-retinyl-N-retinylidene ethanolamine [ 37 ]. Extract of V. uliginosum partially preserved the outer nuclear layer of retina after light damage [ 19 ]. Another study reported the positive effect of V. uliginosum extract on improving learning and memory impairment in murine Alzheimer’s disease model [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants supplementation has been known as effective in alleviating dry eye symptoms [ 16 – 18 ]. In addition, the extract of Vaccinium uliginosum demonstrated protective effect of retinal cells in light-induced retinal damage [ 19 ]. Considering its antioxidative constituents and previous evidences of retinal protection, we hypothesize that the extract of Vaccinium uliginosum will be useful in treating various ocular pathologies including computer vision syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers demonstrated that V. uliginosum extracts protected retinal cells from lightinduced damage [84]. One study investigated the protective action of anthocyanins isolated from V. uliginosum on retinal cells against damage caused by microwave radiation.…”
Section: Ophthalmologymentioning
confidence: 99%